The Function of Class Teacher Educational Management in Improving Student’s Learning Outcomes - Yunita, Erisna; Arafat, Yasir; Mulyadi, Mulyadi (Journal of Social Work and Science Education, 2020)
The purpose of this research was to determine the function of classroom teacher education management in improving student learning outcomes of SD Negeri in Babat Toman District, Musi Banyuasin Regency. This research is a qualitative research, with the aim of being able to gain an in-depth understanding and interpretation of the meaning of the phenomena in the field. The function of classroom teacher education management in improving student learning outcomes of SD Negeri in Babat Toman Subdistrict, Musi Banyuasin Regency can be said to be good and in accordance with the duties assigned in carrying out the learning process.